2013
DOI: 10.1002/mrm.24906
|View full text |Cite
|
Sign up to set email alerts
|

Local shape adaptation for curved slice selection

Abstract: Multidimensional excitation allows imaging of curved slices with constant thickness. It also has the potential for further modification of the slice shape for increased ability to adapt to the anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Recent developments in nonlinear encoding have considered combinations of traditional linear gradients together with curvilinear multipolar fields or quadratic rotation‐symmetric fields . The potential of the SEMs' nonlinearity is that they allow the design of inhomogeneous k‐space sampling patterns for more efficient acquisitions . If we neglect relaxation effects, the magnetic resonance signal sq from the q ‐th RF channel in a multichannel array with nc elements, should satisfy the following equation , sq(t)=Ωm(boldx)Cq(boldx)eiΦ(x,t)dx where m(boldx) is the magnetization at location boldx = [x,y,z] T , Cq(boldx) is the sensitivity of q th coil, and the integral is over Ω, the region of interest.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in nonlinear encoding have considered combinations of traditional linear gradients together with curvilinear multipolar fields or quadratic rotation‐symmetric fields . The potential of the SEMs' nonlinearity is that they allow the design of inhomogeneous k‐space sampling patterns for more efficient acquisitions . If we neglect relaxation effects, the magnetic resonance signal sq from the q ‐th RF channel in a multichannel array with nc elements, should satisfy the following equation , sq(t)=Ωm(boldx)Cq(boldx)eiΦ(x,t)dx where m(boldx) is the magnetization at location boldx = [x,y,z] T , Cq(boldx) is the sensitivity of q th coil, and the integral is over Ω, the region of interest.…”
Section: Theorymentioning
confidence: 99%
“…Other researchers have taken more empirical approaches to designing nonlinear encoding trajectories, such as the MDE work by Lin (20) and optimization schemes being pursued by Layton et al (21). Much effort has also gone into improving the reconstruction algorithms for data obtained with nonlinear SEMs (22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Although the proposed methods create locally linear gradient fields, these fields can also be regarded as N‐SEMs in general. N‐SEMs have proven to be useful in many aspects of both the reception and excitation phases of an imaging sequence. Therefore, increased hardware complexity is useful for many other purposes in addition to multi‐slice excitation with a single‐band RF pulse.…”
Section: Discussionmentioning
confidence: 99%
“…In the reception phase of a pulse sequence, the N‐SEMs are utilized in accelerating the scan, reducing the FOV, reducing the peripheral nerve stimulation (PNS), and increasing the resolution at the periphery of the object . For the excitation part of a pulse sequence, it has been shown that the N‐SEMs can be used to excite curved slices, reduce the FOV with localized excitation, and reduce the SAR, in addition to the B 1 + inhomogeneity correction. Additionally, the dynamic shimming methods using time‐varying higher‐order spatial field terms can be considered as an application for the N‐SEMs.…”
Section: Discussionmentioning
confidence: 99%